a Case of COVID-19 with No Pulmonary Involvement; but with Mediastinal and Subcutaneous Emphysema - Hamid Talebzadeh; Sadegh Mazaheri-Tehrani; mohammad fakhrolmobasheri (Case Reports in Clinical Practice, 2023)
Spontaneous pneumomediastinum (SPM) is a rare clinical entity. In the normal population, it is more likely to occur in people with conditions including chronic obstructive pulmonary diseases and asthma. In the context of COVID-19 few cases of SPM have been reported which most of them were patients with severe lung parenchymal inflammation or patients under mechanical ventilation. In this case, we report a young male with a history of minor childhood asthma who presented with acute dyspnea, forceful coughs, and subcutaneous emphysema. Chest computed tomography had no clues for COVID-19, however, pneumomediastinum and subcutaneous emphysema were obvious. He was primarily diagnosed with acute asthma exacerbation causing SPM but eventually, he tested positive for SARS-COV-2, therefore, he underwent the standard treatment for COVID-19 and the SPM was managed conservatively. Finally, after 12 days of hospitalization, he was discharged in favorable clinical condition.